Assistance teachers of SD Muhammadiyah 20 Sidorejo in using interactive Microsoft Team : Informatics Study Program ITS PKU Muhammadiyah, Surakarta - Nurul Kholisatul ‘ulya; Suryanto Nugroho (Peneliti Teknologi Teknik Indonesia, 2022)
The COVID pandemic has entered its second year. Muhammadiyah 20 elementary school, Sidorejo used online learning applications to support learning during the pandemic, specifically the Microsoft team. So far, Microsoft Teams has been used for video conferencing, assigning tasks, and sending learning videos where students are expected to learn a lot on their own. The learning process requires interesting and enjoyable interactions to increase students' interest. Community service team members provided training and mentoring by utilizing advanced and interactive media, such as delivering material using whiteboards and giving quizzes using Kahoot, integrated with the Microsoft team. In addition to training, teachers were mentored to facilitate its application in learning. The final stage was evaluation. The teachers enthusiastically participated in the training, and there was feedback and discussion during the training. The majority of teachers found it easy to implement the integrated MS. Whiteboard during the mentoring stage. It revealed that the Kahoot application for interactive learning was simple to use. The two applications collaborated to support interactive learning, especially online learning.